(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2023)
The purpose of this study was to translate to Brazilian Portuguese and to analyze the content validity of the Leisure Attitude Scale (LAS), thus proposing the Brazilian version of the instrument, the Brazilian Leisure Attitude Scale (EAL). Following the criteria established by Herdman, Fox-Rushby e Badia (1998), the methodology used for transcultural translation and adaptation, the conceptual, item, semantic, operational and measurement equivalences were respected. The stages of the process were: translation and back-translation, technical review, language clarity assessment, practical relevance and theoretical relevance, application of the focus group tools; retest, and, finally, the application of the completed instrument. The study included adults of both sexes, workers from the industrial sector of Greater Florianopolis - SC / Brazil. The sample consisted of 180 workers for analysis of reproducibility and 992 for indicators of internal consistency. In addition, eleven experts in the field of leisure have contributed to the process of cross-cultural adaptation and content validity of the instrument. The authors attributed satisfactory values ​​to the content analysis in terms of clarity and language (CVCt = 0.818), practical relevance (CVCt = 0.782) and theoretical relevance (X = 3.91, SD = 0.83). The reproducibility indices by the intra-class correlation in test-retest were considered adequate in all domains of LAS (cognitive = 0.785- good, emotional = 0.847 - optimal, behavioral = 0.923 - excellent). In addition, Cronbach’s Alpha presented a value of 0.958. We can say that the Brazilian version of LAS, the EAL is a valid instrument for the investigation of adults’ attitudes towards leisure in the cognitive, affective and behavioral domains, presenting adequate psychometric indicators of validity, reproducibility and internal consistency.